2021
DOI: 10.24940/theijhss/2021/v9/i6/hs2105-042
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Environment and Business Failure: A Study of Small and Medium Scale Enterprises (SMEs) in Northern Nigeria

Abstract: Marketing environment can be seen as those actors and forces that hinder the ability of the marketing manager to achieve competitive advantage. The success of an organization largely depends on how well it defines, understands and faces changes in its marketing environment. The reason for this is that organizations are assumed to be an open system, as interaction between these organizations and their marketing environment is inevitable. Marketing environmental factors include;macro environment otherwise non as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…A study conducted by Fatoki (2011) revealed that financial capital is positively related to SME performance in South Africa. Abdullahi, Ghazali, Awang, Tahir and Salim (2015) found that finance has a positive and significant effect on the performance of SMEs in Nigeria. This discussion suggests the following hypothesis: H2: Financial capital has a positive influence on business performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Fatoki (2011) revealed that financial capital is positively related to SME performance in South Africa. Abdullahi, Ghazali, Awang, Tahir and Salim (2015) found that finance has a positive and significant effect on the performance of SMEs in Nigeria. This discussion suggests the following hypothesis: H2: Financial capital has a positive influence on business performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 1 shows the regression analysis on intrapreneurship training and development as it enhances intrapreneurship and organisational productivity. (Abdullahi, Jakada & Kabir, 2016). Therefore, organisational dynamics and diversity management is essential for growth and economic development.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Creative commons license. To see the complete license contents, please visit http://creativecommons.org/licenses/by-nc/4.0/ performance MSMEs resulting to closure (Abdullahi, Jakada, & Kabir, 2016;Diabate, Allate, Wei, & Yu, 2019;Hamza, Mutala, & Antwi, 2015;Sibanda & Manda, 2016;Wach & Tarus, 2021). Hence, if the above-mentioned issues are not addressed, MSMEs cannot contribute much to the economic development and expectations of commitment policies such as Sustainable Development Goals by the UN, Africa Agenda 2063, and Vision 2030.…”
Section: Introductionmentioning
confidence: 99%